Contraception storage equipment and medicines in first-level health facilities - Rachmawati Felani Djuria (Jurnal Kesehatan Ibu dan Anak, 2020)
In the management of contraceptive equipment and medicine, the program provided by the government still encounters various problems including the occurrence of a vacancy (stock out), buildup in provincial and district warehouses, and the distribution mechanism of contraceptive equipment and medicine that are not smooth. The purpose of this study is to determine the storage of contraceptive equipment and medicine in First Level Health Facilities. The study was conducted with a descriptive observational type with a cross-sectional qualitative approach using interview guidelines. This research was conducted in Bangka Regency and Central Bangka Regency in May-December 2018. The number of respondents was 69 people consisting of the Health Office, Office of Population Control and Family Planning for Women's Empowerment and Child Protection, and First Level Health Facilities. The results showed that the storage of contraceptive devices and drugs in first-level health facilities in Bangka Regency was appropriate with Head Regulation of National Population and Family Planning Agency number 286 / PER / B3 / 2011 concerning Implementation Guidelines Reception, Storage and Distribution of contraceptive equipment and medicine National Population and Family Planning Programs were 3 (23.1%) health facilities, while those that were not appropriate were 10 (76.9%) health facilities. In Central Bangka Regency as many as 3 (33.3%) appropriate health facilities and 6 (66.7%) were not appropriate. Most of the first-level health facilities do not store contraceptives and drugs according to implementation guidelines.